(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Mathematics is often perceived as a challenging subject, provoking a range of emotions from enthusiasm to anxiety among students. However, its significance in general secondary education cannot be overstated. Beyond being a subject to pass exams, mathematics equips students with critical thinking skills, problem-solving abilities, and a foundation for various careers. Mathematics is more than just numbers and equations; it is a tool that enhances cognitive abilities. The process of learning and applying mathematical concepts stimulates the brain, fostering logical reasoning, analytical thinking, and strategic planning.